Radio-climatology of India : Radio Refractive Index near the ground surface (MAUSAM, 1966)
Based on the 5.year averages of the values of pressure, temperature and relative humidity near the ground surface corresponding values of radio refractive index have been computed for 36 stations in India. These data have then been used to describe and discuss the monthly and seasonal distribution of the radio refractive index near the ground. An exhaustive set of radio climatic charts have been prepared and the prominent fei1tures of the ground radio refractive index climate have been discussed. An attempt has been made to delinci1te homo climes of radio climate m India.